2019
DOI: 10.1002/ped4.12164
|View full text |Cite
|
Sign up to set email alerts
|

Updates on management of pediatric obstructive sleep apnea

Abstract: Obstructive sleep apnea ( OSA ) affects about 1%–5% of the pediatric population. The consequences of untreated OSA in children include neurocognitive deficits, behavioral problems, poor school performance as well as systemic and pulmonary hypertension. The treatment options for pediatric OSA are numerous with a variety of surgical and non‐surgical interventions. As our understanding of the complexities of OSA grows, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 87 publications
0
7
0
1
Order By: Relevance
“…1). Although FIS1 is believed to be one of the DRP1 adaptor proteins, recent evidence suggests that FIS1 may instead regulate mitochondrial morphology by inhibition of fusion [38]. In addition, several reports have suggested that FIS1 may be important for mitochondrial quality control by stimulating mitophagy [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…1). Although FIS1 is believed to be one of the DRP1 adaptor proteins, recent evidence suggests that FIS1 may instead regulate mitochondrial morphology by inhibition of fusion [38]. In addition, several reports have suggested that FIS1 may be important for mitochondrial quality control by stimulating mitophagy [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still controversial whether sedation mimics real sleep. It is the reality of the physiological information determined in another discussion [27].…”
Section: Clinical Examinationmentioning
confidence: 97%
“…It is based on the multi-channel recording principle during sleep in accredited sleep laboratories. A typical montage would include several electroencephalography (EEG) channels, chin and anterior tibial electromyography (EMG), bilateral electrooculography, pulse oximeter and pulse waveform, nasal pressure transducer, oronasal airflow thermistor, end-tidal capnography, chest and abdominal respiratory inductance plethysmography, body position sensor, microphone, and real-time synchronized video monitoring [27].…”
Section: Psgmentioning
confidence: 99%
“…Because of this, other interventions should be considered in this population. Continuous Positive Airway Pressure (CPAP) therapy is a treatment for those with OSAS, who are not surgical candidates, or who have residual OSA despite T&A [ 17 , 18 ]. CPAP has been shown to be effective and safe in children [ 19 ].…”
Section: Introductionmentioning
confidence: 99%